More Than Just a Periodontal Pathogen –the Research Progress on Fusobacterium nucleatum - Chen, Yuanxin; Huang, Zhijie; Tang, Zhengming; Huang, Yisheng; Huang, Mingshu; Liu, Hongyu; Ziebolz, Dirk; Schmalz, Gerhard; Jia, Bo; Zhao, Jianjiang (Frontiers in Cellular and Infection Microbiology, 2022)
Fusobacterium nucleatum is a common oral opportunistic bacterium, which can cause a variety of infections. In recent years, studies have shown that Fusobacterium nucleatum is enriched in the related lesions of periodontal disease, halitosis, dental pulp infection, oral cancer and systemic diseases. Thereby, it can promote the initiation and/or progression of these conditions. This article reviews the research progress on Fusobacterium nucleatum in oral and systemic diseases, including epidemiological evidence, possible pathogenic mechanisms and treatment methods. New viewpoints resulting from recent studies can help to understand the role of Fusobacterium nucleatum in the host and provide a basis for finding new methods for diagnosis and treatment of Fusobacterium nucleatum-related diseases.